Body mass index distinctly modulates the associations between Alistipes and CRP/IL-6 in metabolic and lupus inflammatory features - Lourdes Chero-Sandoval; Andrea Higuera-Gómez; Begoña de Cuevillas; Raquel Castejón; María Martínez-Urbistondo; Susana Mellor-Pita; Víctor Moreno-Torres; Daniel de Luis; Amanda Cuevas-Sierra; J. Alfredo Martínez (PLoS ONE, 2025)
Several investigations have documented relationships between body mass index (BMI) and gut microbiota composition in the context of inflammation. However, the precise interaction between BMI and gut microbiota influencing inflammatory markers is still unclear, presenting a challenge for personalized interventions. This study aimed to analyze anthropometric, biochemical and inflammatory variables of participants with systemic lupus erythematosus (SLE) compared to those with low-grade metabolic inflammation (MI), as well as to elucidate the impact of gut microbiota composition, particularly Alistipes , in relation to adiposity, as assessed by BMI, on inflammatory markers within the METAINFLAMATION cohort. A total of 127 adults diagnosed with both diseases, categorized according to the WHO definition of obesity (BMI ≥ 30 kg/m 2 ) and phenotypically analyzed by 16S sequencing of fecal samples. The results showed that patients with low-grade MI had higher anthropometric values, glycosylated hemoglobin and triglyceride levels. On the other hand, patients with SLE and high BMI showed elevated insulin, CRP, and fibrinogen levels, alongside significant changes in Alistipes abundance. Notably, CRP levels were influenced by both BMI and Alistipes, particularly in lupus individuals with higher BMI, and elevated IL-6 was associated with higher CRP in this subgroup. CRP levels are influenced by BMI and Alistipes shahii abundance, especially in lupus individuals with higher BMI. In addition, elevated IL-6 concentrations are significantly associated with more elevated CRP levels in SLE individuals with higher BMI. These findings showed that CRP levels are influenced by BMI and Alistipes, particularly in lupus individuals with higher BMI and highlight the need for personalized approaches based on body composition, inflammatory markers and gut microbiota in patients with lupus and obesity for improving clinical management and outcomes.